Reality-based leadership ditch the drama, restore sanity to the workplace, and turn excuses into results - Wakeman, Cy. (San Francisco Jossey-Bass, 2010)
"Leadership strategies grounded in reality and focused on results. Recent polls show that 71% of workers think about quitting their jobs every day. That number would be shocking-if people actually were quitting. Worse, they go to work, punching time clocks and collecting pay checks, while completely checked out emotionally. In Reality-Based Leadership, expert Fast Company blogger Cy Wakeman reveals how to be the kind of leader who changes the way people think about and perceive their circumstances-one who deals with the facts, clarifies roles, gives clear and direct feedback, and insists that everyone do the same-without drama or defensiveness. Filled with dynamic examples, innovative tools, and diagnostic tests, this book shows you how to become a Reality-Based Leader, revealing how to: *Uncover destructive thought patterns with yourself and others *Diffuse drama and lead the person in front of you *Stop managing and start leading, empowering others to focus on facts and think for themselves *Equipped with a facts-based, confident approach, you will free yourself from the frustrations you face at work and transform yourself into a Reality-Based Leader, with the ability to liberate and inspire others."
Includes bibliographical references Index
Keywords: Leadership